Municipal management and quality of service in the Provincial Municipality of Abancay, 2021 - Cruz Aguilar , Oscar (2022)
The objective of the research has been to determine the relationship that exists between municipal management and the quality of service in the Provincial Municipality of Abancay, 2021. In this sense, a questionnaire has been applied to 384 citizens to know their perception of these variables. With the data collected, we organized a database in SPSS software, with which we were able to describe the behavior of the variables and infer whether there was a significant relationship between them or, on the contrary, they were independent, using the chi square test for this. because the variables are qualitative and we have more than 50 data per variable. According to the results of the investigation, it has been shown that there is a significant relationship between municipal management and the quality of service in the Provincial Municipality of Abancay, 2021.